Visualizing Logical Correlation in Trace Data for System Debugging. - Liu, Chen (Computer (00189162), 2021)
This article describes a mechanism that enables debug engineers to extract and visualize the logical correlation among events and messages in system-level trace data. It enables debug engineers to focus only on trace packets that are logically correlated to the issue under debug.